DENTAL HEALTH PROBLEMS AMONG SANTRI AT ISLAMIC BOARDING SCHOOLS IN MEDAN, NORTH SUMATERA - Tri Bayu Purnama; Samsul Askhori; Devi Juliana Pohan; Dwichy Augie (Poltekkes Kemenkes Semarang, 2021)
Dental health remains a public health problem with increased the prevalence of dental problems from 2007 to 2013. The problem is highest in the early adolescent age group. A dental problem occurs due to lack of behavior on the routine toothbrush (2.8%). The purpose of this study was to describe dental problems in Islamic boarding schools in Medan. This study used a cross sectional design in seven Islamic boarding schools in Medan with a total sample of 436 students in the 5.319 total population. System random sampling was applied in this study and the questionnaire was distributed to sample. The data analysis used was descriptive frequency. The results showed that the behavior of brushing teeth based on age group was highest in the early adolescent group in the category of brushing teeth in the morning (78%) and afternoon (92%). Based on gender, both men and women showed the highest tooth brushing behavior in the morning (37.8%; 40.4%) and afternoon (45.9%; 46.6%). Dental health problems by age group were included in the category of healthy teeth (49.1%). Based on gender also showed dental problems for both men and women (25.9%; 24.1%) in the category of healthy teeth. Dental health among female students is still found to have dental health problems caused by the behavior of brushing teeth that is not in accordance with the recommendations of the Ministry of Health, namely after breakfast and before going to bed at night.